Georgia O'Keeffe's Wartime Texas Letters - O'Keeffe, Georgia, 1887-1986 (Book collections on Project MUSE., 2020)
"This work focuses on O'Keeffe's words rather than her images. Von Lintel aims to allow the artist's voice to 'emerge as a powerful witness of her own life, but also of western America in a pivotal moment of its development.' The result is an important new examination of one of our most important artists during a time when she was in the process of discovering her future identity"--